2022
DOI: 10.3389/fmars.2022.925567
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Human Activities and Environmental Changes on Spatial-Seasonal Variations of Metals in Surface Sediments of Zhanjiang Bay, China

Abstract: This study investigated the total concentrations and geochemical compositions of metals (Cd, Cr, Cu, Ni, Pb, Zn, Fe and Mn) in surface sediments of Zhanjiang Bay (ZJB) in spring and summer, to assess the contamination status, mobility and influencing factors of spatial-seasonal changes of these metals. The average total concentration for each studied metal in the surface sediments of ZJB was 0.173 μg/g for Cd, 58.25 μg/g for Cr, 17.11 μg/g for Cu, 16.89 μg/g for Ni, 28.70 μg/g for Pb, 67.91 μg/g for Zn, 30.18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Numerous studies in the related literature reported that clay, silt, and organic matter particles are important carriers of TEs in sediments (Rubio et al, 2000;Vaalgamaa and Korhola, 2004;Selvam et al, 2012;Özkan, 2012;Dou et al, 2013;Hu et al, 2013;Xu et al, 2016;Zhao et al, 2017;Perina et al, 2018;Remeikaite-Nikienėet al, 2018;Sun et al, 2020; Values of Pearson correlation coefficient (r) highlighted in bold are different from 0 with a significance level a = 0.05. Wang et al, 2021;Zhou et al, 2022). On the one hand, the finer sediment fractions (clay and silt) have a higher specific surface area than the coarser fraction (sand), giving them more binding sites for the adsorption of TEs and organic matter (Rubio et al, 2000;Xu et al, 2016;Zhou et al, 2022).…”
Section: Element Concentrations In Surface Sediments and Potential Co...mentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous studies in the related literature reported that clay, silt, and organic matter particles are important carriers of TEs in sediments (Rubio et al, 2000;Vaalgamaa and Korhola, 2004;Selvam et al, 2012;Özkan, 2012;Dou et al, 2013;Hu et al, 2013;Xu et al, 2016;Zhao et al, 2017;Perina et al, 2018;Remeikaite-Nikienėet al, 2018;Sun et al, 2020; Values of Pearson correlation coefficient (r) highlighted in bold are different from 0 with a significance level a = 0.05. Wang et al, 2021;Zhou et al, 2022). On the one hand, the finer sediment fractions (clay and silt) have a higher specific surface area than the coarser fraction (sand), giving them more binding sites for the adsorption of TEs and organic matter (Rubio et al, 2000;Xu et al, 2016;Zhou et al, 2022).…”
Section: Element Concentrations In Surface Sediments and Potential Co...mentioning
confidence: 99%
“…Wang et al, 2021;Zhou et al, 2022). On the one hand, the finer sediment fractions (clay and silt) have a higher specific surface area than the coarser fraction (sand), giving them more binding sites for the adsorption of TEs and organic matter (Rubio et al, 2000;Xu et al, 2016;Zhou et al, 2022). On the other hand, the organic matter coatings in these fine-grained sediments retain a variety of TEs (Rubio et al, 2000).…”
Section: Element Concentrations In Surface Sediments and Potential Co...mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that higher heavy metal contaminations were observed around the southern coast of Hainan Island, which likely originated from pollution discharge by intensive human activities, such as industrial discharges from port and shipping facilities, agriculture wastes, domestic sewage and frequently fishing activities (Yang et al, 2004;Li and Huang, 2012;Wang et al, 2013;Yang et al, 2019). In addition, with the rapid development of urbanization and industrialization, higher heavy metal contaminations have also been found in the Pearl River Estuary and the coastal waters of western Guangdong Province (Li et al, 2007;Zhang et al, 2010;Zhang et al, 2015;Zhang et al, 2018;Zhang et al, 2022b;Zhou et al, 2022). The higher heavy metal contamination in those regions would enter into the Beibu Gulf with the water masses, resulting in higher concentrations of heavy metals occurring in the offshore areas of the Beibu Gulf.…”
Section: Contaminated Characteristics Of Heavy Metals In Seawater Of ...mentioning
confidence: 99%